The impact of HIV infection and men who have sex with men status on hepatitis A infection: The experience of two tertiary centres in Northern Italy during the 2017 outbreak and in the 2009‐2016 period. Issue 6 (25th March 2019) - Lombardi, Andrea; Rossotti, Roberto; Moioli, Maria Cristina; Merli, Marco; Valsecchi, Pietro; Zuccaro, Valentina; Vecchia, Marco; Grecchi, Cecilia; Patruno, Savino F. A.; Sacchi, Paolo; Fabbiani, Massimiliano; Puoti, Massimo; et al.
Summary: Hepatitis A is a self‐limiting infection representing the most common cause of viral hepatitis worldwide. Despite being a low incidence region, in the European Union, an increasing number of cases have been reported since summer 2016, resulting in a large outbreak in 2017, involving mainly men who have sex with men (MSM). Some reports described a different clinical course of hepatitis A virus in patients infected by human immunodeficiency virus (HIV) or MSM. We consecutively collected all the hospitalized cases of hepatitis A referred to two tertiary centres in Northern Italy in 2017 and retrospectively analysed the electronic records of the 2009‐2016 period (pre‐2017). We evaluated demographics data, risk factors, comorbidities and laboratory results to see whether MSM status or HIV infection influenced the disease. Overall, 117 cases were identified in 2017:107 (91%) were male, 78 reported themselves as MSM (66%) and 17 (14.5%) were infected by HIV. For the pre‐2017 period, 48 cases were reported: 29 (60%) were male and 3 (6.2%) were infected by HIV. After stratification for HIV infection, MSM status and occurrence period, no differences were found in aspartate aminotransferase, alanine aminotransferase, γ‐glutamyl transpeptidase; bilirubin, alkaline phosphatase and bilirubin values, hospitalization length, HIV viral load and CD4 + cells count. HIV‐positive patients presented a higher number of patients with INR > 1.5 at admission. MSM status and HIV infection did not affect neither the clinical course nor the severity of hepatitis A.